Cultural context in parliamentary discourse with examples of parallel speeches in the polish Sejm and the German Bundestag – reflections from a translator’s perspective - Jurewicz, Magdalena (Lingua Posnaniensis, 2018)
The article presents examples of cultural references made by Polish MPs speaking in the Polish Sejm and German MPs speaking in the German Bundestag. The term “cultural context” will be used as defined by Boniecka (1994). There will be presented two examples of parliamentary speeches given in the Polish Sejm and the German Bundestag from a larger corpus of collected data for the purpose of the research on the appellative function of the word “wish”. The starting point for compiling texts was the minutes of the parliamentary debates of the Polish Sejm which contained the word “życzyć” (“wish” in Polish) and the minutes of parliamentary debates in the Bundestag which contained the word “wünschen” (‘wish” in German) in the first person singular and plural. The topic of the speeches had a secondary meaning. On the basis of the examples it discussed will be shown that parallel texts of MP’s speeches are a valuable teaching material in specialised language lessons.